Alcohol Addiction Among High School Students in Pamekasan Regency: The Impact of Parental Supervision - Oktafiana, Shinta; Romadhon, Sahrul; Risdiana, Faraniena Yunaeni; Rahman, Muhammad Hadiatur; Gunawan, Jessie (IAIN Madura, 2024)
This study was motivated by the large number of adolescents who consume alcoholic beverages, so researchers wanted to know the factors that cause adolescents to consume alcohol and how the role of parents in dealing with these problems. The purpose of this study is that parents are expected to be able to provide education to be careful with their association so as not to fall into negative things such as juvenile delinquency in the form of drinking drinks containing alcohol where these drinks are very dangerous to health because they can affect brain performance so that when attending school the teenager will lose concentration. This research uses a qualitative approach with a phenomenology type. The data sources used are primary and secondary data sources. Primary data sources derived from interviews. While secondary data sources come from documents. Data collection techniques through interviews, observation and documentation. The results showed that the cause of a person becoming an alcoholic is not known with certainty, but alcohol use is not the only causative factor. Of the people who consume alcohol, about 10% become addicts. Some of the reasons individuals consume alcohol include to dare to take risks, calm themselves, overcome themselves, run away from loneliness, forget sadness, feel confident, overcome depression, adjust to social situations, relieve pain, overcome personal stress when many schoolwork. The ease of getting liquor and the loose supervision of parents and the surrounding environment are one of the causes of so many children who consume liquor. In addition, a sense of solidarity and friendship bonds are one of the reasons to try liquor. The role of parents in dealing with these problems is more participatory and passive. Where parents only reprimand and advise and some even do nothing, so that children still cannot escape from alcoholism.